Zmiana systemu wyborczego do rad gmin a łączność z wyborcami - Surówka, Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
The electoral system plays an important role in the process of the determining of the election results. It enables the distribution of the seats among the competing electoral committees, and it affects the balance of the political forces in the representative bodies. But the meaning of the electoral system is not limited to the electoral process. The electoral system affects also the communication of the elected people with the voters. The electoral code introduced important changes in the manner of the conduct of elections to the municipal councils. The purpose of this presentation is an attempt to analyse how much these changes may affect the reinforcement of the ties between the councillor and the voters and they may contribute to better representation of the interests of the electorate in the work of the municipal council.
The change of the electoral system to the municipal council and communication with the voters
Keywords: electoral system; communication with the voters; election; municipal council